EKSPEKTASI HUKUM PROMOSI JABATAN UNTUK PEREMPUAN MENJADI PENGHULU DAN KEPALA KUA: - Ishom, Muhammad (Jurnal Bimas Islam, 2017)
in Serang city of Banten  there are fifteen women civil state apparatus who work in office of Religious Affairs (KUA). They worked in the office for many years but did not get the right to be promoted as penghulu or head office. The reason why women should not be penghulu or head office is the law and legislation norm, especially unauthorized women become marriage guardians (wali hakim). Whereas at Hanafiyah Mazhab there is an opinion that allows women to take the judge position. This article describes the women law possibility to be become penghulu or head oofice at KUA, legally and normatively Ada lima belas ASN (aparatur sipil negara) perempuan yang telah lama bertugas di KUA Kecamatan se-Kota Serang akan tetapi tidak ada yang dipromosikan menjabat menjadi penghulu maupun kepala kantor KUA. Di antara alasan mereka tidak berhak menjadi pejabat pencatat nikah adalah karena salah satu tugas yang melekat pada jabatan itu terdapat wali hakim yang didominasi laki-laki. Padahal dalam mazhab Hanafi ada pendapat yang membolehkan perempuan menduduki jabatan hakim. Dalam tulisan ini dijelaskan kemungkinan hukum perempuan menjadi penghulu maupun kepala KUA menurut hukum dan ketentuan normatif.